How language affects children's use of derivational morphology in visual word and pseudoword processing: evidence from a cross-language study - Casalis, Séverine; Quémart, Pauline; Duncan, Lynne G. (Frontiers in Psychology, 2015)
Developing readers have been shown to rely on morphemes in visual word recognition across several naming, lexical decision and priming experiments. However, the impact of morphology in reading is not consistent across studies with differing results emerging not only between but also within writing systems. Here, we report a cross-language experiment involving the English and French languages, which aims to compare directly the impact of morphology in word recognition in the two languages. Monolingual French-speaking and English-speaking children matched for grade level (Part 1) and for age (Part 2) participated in the study. Two lexical decision tasks (one in French, one in English) featured words and pseudowords with exactly the same structure in each language. The presence of a root (R+) and a suffix ending (S+) was manipulated orthogonally, leading to four possible combinations in words (R+S+: e.g. postal; R+S-: e.g. turnip; R-S+: e.g. rascal; and R-S-: e.g. bishop) and in pseudowords (R+S+: e.g. pondal; R+S-: e.g. curlip; R-S+: e.g. vosnal; and R-S-: e.g. hethop). Results indicate that the presence of morphemes facilitates children’s recognition of words and impedes their ability to reject pseudowords in both languages. Nevertheless, effects extend across accuracy and latencies in French but are restricted to accuracy in English, suggesting a higher degree of morphological processing efficiency in French. We argue that the inconsistencies found between languages emphasise the need for developmental models of word recognition to integrate a morpheme level whose elaboration is tuned by the productivity and transparency of the derivational system.